2014
DOI: 10.1016/j.cell.2013.12.023
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Triggers Golgi Dispersal via DNA-PK and GOLPH3

Abstract: SUMMARY The response to DNA damage, which regulates nuclear processes such as DNA repair, transcription, and cell cycle, has been studied thoroughly. However, the cytoplasmic response to DNA damage is poorly understood. Here, we demonstrate that DNA damage triggers dramatic reorganization of the Golgi, resulting in its dispersal throughout the cytoplasm. We further show that DNA-damage-induced Golgi dispersal requires GOLPH3/MYO18A/F-actin and the DNA damage protein kinase, DNA-PK. In response to DNA damage, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
272
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(298 citation statements)
references
References 60 publications
(94 reference statements)
13
272
1
1
Order By: Relevance
“…Screens for S/TQ-containing substrates of ATR and ATM following DNA damage have also revealed putative substrates outside of the nucleus, as well as factors that are not directly linked to DNA repair processes (Matsuoka et al, 2007;Mu et al, 2007;Paulsen et al, 2009), although the functional relevance of many of these phosphorylation events remains to be determined. Intriguingly, DNA-PK has also been located at the Golgi, reinforcing the possibility that other PIKKs might also function outside of the nucleus (Farber-Katz et al, 2014).…”
Section: Signaling Outputs Of Atr and Atmmentioning
confidence: 99%
“…Screens for S/TQ-containing substrates of ATR and ATM following DNA damage have also revealed putative substrates outside of the nucleus, as well as factors that are not directly linked to DNA repair processes (Matsuoka et al, 2007;Mu et al, 2007;Paulsen et al, 2009), although the functional relevance of many of these phosphorylation events remains to be determined. Intriguingly, DNA-PK has also been located at the Golgi, reinforcing the possibility that other PIKKs might also function outside of the nucleus (Farber-Katz et al, 2014).…”
Section: Signaling Outputs Of Atr and Atmmentioning
confidence: 99%
“…31 Recently, a study demonstrated that, in mammalian mitotic cells, DNA damage triggers the Golgi to fragment and disperse throughout the cytoplasm leading to the amplification of the DNA damage response via the DNA damage protein kinase, DNA-PK. 32 This study highlights direct links between the DNA damage response and the Golgi. Thus, the presence of FANCB, FANCM and FANCD2 proteins in the Golgi raised the possibility that the newly synthesized FANC proteins may undergo post-translational modification and store for a period of time prior to being distributed to sites of DNA damage foci at appropriate time points of germ cell development.…”
Section: Discussionmentioning
confidence: 99%
“…GOLPH3 bridges phosphatidylinositol-4-phosphate and actomyosin and thereby drives Golgi dispersal and vesicular budding (3,38). A PITPNC1/ RAB1B protein complex anchors GOLPH3 to the Golgi, facilitating Golgi extension and the release of secretory vesicles containing factors that promote extracellular matrix remodeling and tumor angiogenesis (4).…”
Section: Discussionmentioning
confidence: 99%